Legacies of a Contested Campus: Urban Renewal, Community Resistance, and the Origins of Gentrification in Denver. Issue 9 (21st October 2017) - Page, Brian; Ross, Eric
ABSTRACT: The postwar urban renewal experience varied among US cities according to the result of local social contests pitting those imposing their power to transform urban space against those resisting it. In this paper, we examine the role of one such contest in shaping urban renewal outcomes in Denver, using the case of the late 1960s Auraria project. The project sought to remove a poor, Hispanic neighborhood in order to build a new downtown college campus, generating community opposition from the inner city neighborhood residents, leaders of the city's Chicano Movement, and historic preservation activists. We demonstrate how resistance actively shaped the ultimate form and character of the project, and how the legacies of this urban renewal contest extended—in unforeseen ways—beyond the immediate struggles of the time. We argue that these legacies provide the essential context for understanding planning practice, redevelopment strategies, and gentrification dynamics in the city today.